Hubungan Gaya Kepemimpinan dan Moril Kerja dengan Disiplin Kerja pada Pegawai/Aparatur Pemerintahan SKPD Kecamatan Medan Tuntungan Kota Medan - Rina Amelia; M. Rajab Lubis; Suryani Hardjo (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2019)
This study aims to determine the relationship of leadership style and work morale with work discipline on the staff / government officials SKPD Medan Tuntungan Subdistrict. The data collection instrument used are the scale of work discipline, the scale of leadership style and work morale scale. Population in this research is all the staff / government officials of SKPD Medan Tuntungan District. The sampling technique used samples saturated and the number of samples used is 86 people. Data analysis technique used in this research is multiple regression analysis. The results showed that there was a significant positive relationship between leadership style and work morale with work discipline.The total effective contribution of leadership style and work morale variables to work discipline was 55,9%.